Factor XIII activation peptide is released into plasma upon cleavage by thrombin and shows a different structure compared to its bound form - Schroeder, Verena; Vuissoz, Jean-Marc; Caflisch, Amedeo; Kohler, Hans P. (Thrombosis and Haemostasis, 2007)
The first step of coagulation factor XIII (FXIII) activation involves cleavage of the FXIII activation peptide (FXIII-AP) by thrombin. However, it is not known whether the FXIII-AP is released into plasma upon cleavage or remains attached to activated FXIII. The aim of the present work was to study the structure of free FXIII-AP, develop an assay for FXIII-AP determination in human plasma, and to answer the question whether FXIII-AP is released into plasma. We used ab-initio modeling and molecular dynamics simulations to study the structure of free FXIII-AP. We raised monoclonal and polyclonal antibodies against FXIII-AP and developed a highly sensitive and specific ELISA method for direct detection of FXIII-AP in human plasma. Structural analysis showed a putative different conformation of the free FXIII-AP compared to FXIII-AP bound to the FXIII protein. We concluded that it might be feasible to develop specific antibodies against the free FXIII-AP. Using our new FXIII-AP ELISA, we found high levels of FXIII-AP in in-vitro activated plasma samples and serum. We showed for the first time that FXIIIAP is detached from activated FXIII and is released into plasma, where it can be directly measured. Our findings may be of major clinical interest in regard to a possible new marker in thrombotic disease.
Keywords: factor XIII; activation peptide; activation marker; molecular dynamics simulations